Pendampingan Literasi Digital dan Pengembangan Potensi Diri “Produktif di Dunia Digital” - Ibad, M. Nashoihul (Universitas Islam Internasional Darullughah Wadda'wah, 2024)
This service activity aims to improve digital literacy and develop students' self-potential at MA Ma'arif Pasuruan. Digital literacy is an essential skill in today's digital era, but related learning is still not effectively applied in the Madrasah Aliyah environment. Through this program, assistance is provided to students to arouse enthusiasm to continue to the lecture level and deepen their understanding of digital literacy. The methods used include mentoring, material presentation, training, and discussion. The results of this activity show that students can acquire new skills that can be applied in daily life, strengthening their potential to be more productive in the digital world.